Peningkatan Kemampuan Komunikasi dan Kerjasama Melalui KKN Posdaya di Universitas Mathla’ul Anwar Banten - Asep Sujana; Ika Meika (Universitas Mathla'ul Anwar Banten, 2016)
Universitas Mathla'ul Anwar Banten is one of the university which is located in Pandeglang Regency. It always tries to improve the quality in the service for the society. One of the activities in Mathla’ul Anwar University that has already been done is KKN Posdaya Program. The KKN activity has already been done well, however it needs some improvements in the capacity of the students who are ready to involve themselves in the society. The KKN activity in Mathla'ul Anwar University aims to integrate the education and teaching, research and community service by the students pragmatically, comprehensive dimension through an interdisciplinary approach, comprehensive, and cross-sector. By doing the KKN Activity, it is hoped that the students will be a part of the society that can contribute directly to help the problems in the society. The Approach method for the improvement capacity program of communication and cooperation uses PALS (Participatory Action Learning System) method.